"Can't Wait to Blackout Tonight": An Analysis of the Motives to Drink to Blackout Expressed on Twitter. (10th July 2019) - Riordan, Benjamin C.; Merrill, Jennifer E.; Ward, Rose Marie
Abstract : Background: Alcohol‐related blackouts are associated with a range of negative consequences and are common among social drinkers. Discussing alcohol use on social networking platforms (e.g., Twitter) is common and related to higher alcohol consumption levels. Due to the widespread nature of alcohol‐related social networking posts and alcohol‐related blackouts, we examined the content of alcohol‐related blackouts posts/"Tweets" on Twitter, with a focus on intentions to blackout and specific motivations for blacking out. Methods: A set of Tweets containing "blackout, " "blackout, " "blacking out, " "blacked out, " or "blacks out" were collected from April 26, 2018, and April 29, 2018. Using NVivo software, we coded all preblackout Tweets (i.e., before the blackout experience) for intentions and motives to blackout. Results: Most Tweets that we collected expressed an intention to blackout and these intentions ranged in strength (i.e., will blackout vs. might blackout). With respect to specific motives for blacking out, celebration motives were identified. For example, Tweets addressed blacking out to celebrate one's birthday, someone else's birthday, a school or work accomplishment, a sports win, during a vacation, or a holiday. Another endorsed motive for blacking out was loss or coping motives. For example, the Tweets commented on blacking out to deal with stress or a bad day. Conclusion: Our findings suggest that Twitter users express intentions to blackout due to celebration or coping reasons. Given the consequences associated with blackout drinking, future research should consider the link between blackout intentions, blackout motives, and alcohol‐related harm. Abstract : We examined the content of alcohol related blackout Tweets posted before a blackout to determine whether individuals intended to blackout or had specific motives for blacking out. Most pre‐blackout Tweets expressed intention to blackout ("I'm going to get blackout drunk tonight") and two specific motives were identified: celebration motives (to celebrate a birthday or event) and coping motives (to cope with stress or a bad day). There is a clear need for future research and interventions to consider blackout intentions.